Modeling of hydrogen and organic acid production using different concentrations of sugarcane vinasse under thermophilic conditions and a link with microbial community 16S rRNA gene sequencing data. (10th October 2022) - Couto, P.T.; Eng, F.; Bovio-Winkler, P.; Cavalcante, W.A.; Etchebehere, C.; Fuentes, L.; Nopens, I.; Zaiat, M.; Ribeiro, R.
Abstract: Acidogenesis of sugarcane vinasse at 15 and 20 kgCOD m −3 in a batch bioreactor occurred via acrylate and homoacetogenesis pathways. Both these pathways were incorporated into the Anaerobic Digestion Model Number 1 (ADM1) and they were validated with biomolecular analysis. As a novelty of this work, ADM1 was modiﬁed integrating a new lactate consumption pathway to the model ( L a c t a t e → A c e t a t e + P r o p i o n a t e + H y d r o g e n ) and the homoacetogenesis ( H y d r o g e n + C O 2 → A c e t a t e ) to initial concentrations of vinasse of 15 and 20 kgCOD m −3 . To evaluate the microbial community involved in such fermentative pathways, biomass samples were taken from the reactor operated with vinasse under organic matter concentrations of 15, 20 and 30 kgCOD m −3, which was analyzed by 16S rRNA gene massive sequencing. Moreover, the abundance of hydrogen producing microorganisms and homoacetogens were quantified by q-PCR. It was mathematically demonstrated that the acrylate and homoacetogenesis pathways were able to describe the system at low concentrations of sugarcane vinasse (15 and 20 kgCOD m −3 ) and the microbial community compositions confirmed the presence of microorganisms with the metabolic pathways hypothesized here. Highlights: A model for an acidogenic batch reactor used in vinasse processing was modified. For 15 and 20 kgCOD m −3, the production of propionate and acetate was observed. Acrylate and homoacetogenesis pathways were incorporated into the model. Biomolecular analysis and ADM1 modelling are connected.